OPTIMAL CENTRAL BANK DIGITAL CURRENCY DESIGN FOR EMERGING ECONOMIES - Syarifuddin, Ferry (Journal of Central Banking Law and Institutions, 2024)
The growth of digitalisation presents the possibility for Central Bank Digital Currency (CBDC) to emerge as a secure and efficient payment method. However, despite the benefits, CBDC implementation needs to be adapted to the capabilities and needs of each country. This study uses meta-strength, weakness, opportunity, and threat (meta-SWOT) analysis to assess the internal strengths and weaknesses, as well as the external opportunities and threats, to determine the most optimal CBDC design for emerging economies. In analysing internal aspects, CBDC allows for an efficient payment system, followed by a more effective monetary policy. Furthermore, the technology creates the possibility to boost financial inclusion and trace many illicit activities. However, to achieve that, high investment costs and privacy issues must be accommodated, followed by technological risks such as the digital divide and electrical outages. Turning to external aspects, growing technology, the network effect, enthusiasm for CBDC, and the impracticality of cash usage have become catalysts for CBDC development. Despite these opportunities, central banks should be wary of the threat of cyberattacks, quickening bank disintermediation, legal issues within their respective countries, and competition with private crypto companies. Altogether, the most optimal CBDC design in emerging economies is retail and wholesale coverage, interest-bearing (wholesale) and noninterest-bearing (retail) remuneration, account-based and token-based paymentsystems, a traceable degree of anonymity, hybrid architecture, a Decentralised Ledger Technology (DLT) ledger system, and domestic and cross-border scope. These results are supported by rigorous examination of global CBDC research and development.